Verbal ability, depression, and anxiety as correlates of interrogative suggestibility in children exposed to life adversities. Issue 5 (28th May 2017) - Curci, Antonietta; Bianco, Antonella; Gudjonsson, Gisli H.
ABSTRACT: In the present study, we assess the relationship of verbal ability, depression, and anxiety with interrogative suggestibility (IS) in a sample of children exposed to life adversities and requiring assistance by the governmental social service ( n  = 39), as compared with normal controls ( n  = 36). The Gudjonsson Suggestibility Scale 2 was administered to participants in a battery including measures of memory capacity, verbal ability, depression, and anxiety. The finding showed that the 'assisted' children were significantly more suggestible than the controls with a large effect size for Yield 1 and total suggestibility. In addition, IS was negatively correlated with verbal memory and ability, but not with anxiety and depression. The two groups differed as to their level of total suggestibility after adjusting for verbal ability. Implications of the findings for the forensic assessment of vulnerable subjects are discussed.